The rs696880 Polymorphism in the Nogo-A Receptor Gene (RTN4R) Is Associated With Susceptibility to Sporadic Amyotrophic Lateral Sclerosis in the Chinese Population - Xu, Lianping; Li, Jiao; Tian, Danyang; Chen, Lu; Tang, Lu; Fan, Dongsheng (Frontiers in Aging Neuroscience, 2018)
Single-nucleotide polymorphisms (SNPs) in the Nogo-A receptor gene (RTN4R) have been associated with increased risk for sporadic amyotrophic lateral sclerosis (SALS) in the French population. In the present study, we investigated the associations between RTN4R tag SNPs and SALS in a large Chinese population. Four tag SNPs (rs854971, rs887765, rs696880, and rs1567871) in the RTN4R gene with an r2 threshold of 0.8 and a minor allele frequency (MAF) greater than 0.2% were selected based on Chinese population data from HapMap. A total of 499 SALS patients and 503 healthy controls were genotyped for the SNPs by SNaPshot technology. Haplotype analysis of the four SNPs was performed using the SHEsis software platform. The results showed a significant association between the rs696880 risk allele (A) and SALS in the Han Chinese population (P=0.009, odds ratio (OR)=1.266 [1.06-1.51]). The allele and genotype frequencies of rs854971, rs887765 and rs1567871 were not associated with SALS. The distribution of the GAAT haplotype was different between the case and control groups (P=0.008, OR=1.289 [1.066-1.558]). In conclusion, our study showed an association between the RTN4R SNP rs696880 and the risk of SALS in the Han Chinese population, with the A allele increasing risk.